2017
DOI: 10.1016/j.vaccine.2017.01.071
|View full text |Cite
|
Sign up to set email alerts
|

Post-hoc analysis of a randomized controlled trial: Diabetes mellitus modifies the efficacy of the 13-valent pneumococcal conjugate vaccine in elderly

Abstract: Among immunocompetent elderly, VE of PCV13 was modified by DM with higher VE among subjects with DM. Significant effect modification was not observed for subjects with heart disease, respiratory disease, smoking, or presence of any comorbidity. CAPiTA trial registration number: www.ClinicalTrials.gov; trial number NCT00744263.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 18 publications
3
15
0
10
Order By: Relevance
“…Huijts et al retrospectively obtained information on comorbidities from medical records (from GPs, hospitals) for participants who were identified with vaccine-type CAP (n=139), and from ICPC codes from general practitioners for 40 427 CAPITA participants. The number of individuals with comorbidities was higher when data were obtained from medical records rather than from self-report [12]. This could suggest that the population in CAPITA actually was less healthy than previously reported.…”
Section: Evidence Base For Pcv13mentioning
confidence: 67%
See 2 more Smart Citations
“…Huijts et al retrospectively obtained information on comorbidities from medical records (from GPs, hospitals) for participants who were identified with vaccine-type CAP (n=139), and from ICPC codes from general practitioners for 40 427 CAPITA participants. The number of individuals with comorbidities was higher when data were obtained from medical records rather than from self-report [12]. This could suggest that the population in CAPITA actually was less healthy than previously reported.…”
Section: Evidence Base For Pcv13mentioning
confidence: 67%
“…Nine studies reported on PCV13 VE [11][12][13][14][15][16][17][18][19] (Table 1). Five of these were post-hoc analyses based on CAPITA data [11][12][13][14][15]. Besides the post-hoc studies, we identified two cohort studies, one from Spain [16] and one from Germany [17], and two studies using test-negative design (TND), one from the US [18] and one from Italy [19].…”
Section: Conjugate Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…Смертность от пневмонии у пациентов с СД в 1,7 раза выше, а от сепсиса -в 3,3 раза выше, чем у пациентов без СД. Более высокую смертность от пневмонии у взрослых с СД связывают с ухудшением имеющейся у них сердечно-сосудистой патологии или имеющимся риском острого повреждения почек после перенесенной пневмонии, которое, как предполагают, развивается на фоне имевшего место субклинического поражения почек [ [23]. Было показано, что эффективность вакцинации ПКВ13 у пациентов с CД составила 89,5% (95% ДИ 65,5-96,8), что достоверно выше эффективности вакцинации у пациентов, имеющих сердечно-сосудистые заболевания, патологию респираторного тракта, курящих или с наличием любого другого фактора риска.…”
Section: вакцинация против пневмококковой инфекцииunclassified
“…Bunlardan birinde aşı tipine özgü TGP'nin ve İPH'nin önlenmesiyle ilgili aşı etkinliği, KPA13 ile aşılan-dıkları sırada 65 yaşında olan kişilerde %65 iken, 75 yaşında olanlarda %40 olarak bulunmuştur (77). KPA13 ile aşılandık-ları sırada diyabetik olan ≥65 yaşındaki immünokompetan erişkinlerde, diyabetik olmayanlardakinden daha yüksek bir aşı etkinliği görülmüş; kalp, solunum ve karaciğer hastalığı, aspleni ve tütün kullanımı gibi diğer komorbiditeler ise aşı etkinliğini değiştirmemiştir (78). PCV13'ün uygulandığı eriş-kinlerde 13 serotipin tümüne karşı OPA titrelerinde ve IgG konsantrasyonlarında gözlenen anlamlı artışlar, 2 yıl sonra da korunmuştur (79).…”
Section: Kpa13 ≥50 Yaşındaki Erişkinler Için 2011'de Ab'de European unclassified